Chromosome polymorphisms track trans‐Atlantic divergence and secondary contact in Atlantic salmon. Issue 8 (29th April 2019) - Lehnert, Sarah J.; Bentzen, Paul; Kess, Tony; Lien, Sigbjørn; Horne, John B.; Clément, Marie; Bradbury, Ian R.
Abstract: Pleistocene glaciations drove repeated range contractions and expansions shaping contemporary intraspecific diversity. Atlantic salmon ( Salmo salar ) in the western and eastern Atlantic diverged >600, 000 years before present, with the two lineages isolated in different southern refugia during glacial maxima, driving trans‐Atlantic genomic and karyotypic divergence. Here, we investigate the genomic consequences of glacial isolation and trans‐Atlantic secondary contact using 108, 870 single nucleotide polymorphisms genotyped in 80 North American and European populations. Throughout North America, we identified extensive interindividual variation and discrete linkage blocks within and between chromosomes with known trans‐Atlantic differences in rearrangements: Ssa01/Ssa23 translocation and Ssa08/Ssa29 fusion. Spatial genetic analyses suggest independence of rearrangements, with Ssa01/Ssa23 showing high European introgression (>50%) in northern populations indicative of post‐glacial trans‐Atlantic secondary contact, contrasting with low European ancestry genome‐wide (3%). Ssa08/Ssa29 showed greater intrapopulation diversity, suggesting a derived chromosome fusion polymorphism that evolved within North America. Evidence of potential selection on both genomic regions suggests that the adaptive role of rearrangements warrants further investigation in Atlantic salmon. Our study highlights how Pleistocene glaciations can influence large‐scale intraspecific variation in genomic architecture of northern species.